Myeloid-derived suppressor-like cells – does their frequency change in patients with different stages of CRC? - Brčerević, Irina; Doder, Radoje; Perišić, Nenad; Petrović, Stanko; Vojvodić, Danilo (Vojnosanitetski pregled, 2023)
Background/Aim. Colorectal cancer (CRC) is one of the most common cancers in the population, often leading to lethal outcomes. Myeloid-derived suppressor cells (MDSCs) belong to a heterogeneous group of immature cells thought to have an immunosuppressive effect that may aid in tumor development and spreading. The aim of this study was to analyze the frequency and significance of MDSC-like cells at different stages in patients with CRC. Methods. Peripheral blood (PB) samples of 83 patients at different stages of the disease and 12 healthy subjects (control group) were analyzed. MDSC-like cells were identified and enumerated in the PB samples of the participants based on the immunophenotypic characteristics of the cells. Results. A statistically significant increase in the absolute and relative number of polymorphonuclear (PMN) MDSC (PMN-MDSC)-like cells was observed in the PB of all the patients with CRC, compared to the healthy control group (p < 0.0001). No significant increase was observed in monocytic MDSC (M-MDSC)-like cells when they were analyzed without CRC stage stratification (p > 0.05). When the relative and absolute numbers of PMN-MDSC-like cells were analyzed in relation to the stages of CRC disease (TNM classification), a statistically significant difference was observed between the control group and patients in stages III and IV of the disease (p = 0.0005 vs. p = 0.0003 and p < 0.0001 vs. p
Keywords: colorectal neoplasms; myeloid-derived suppressor cells; neoplasm metastasis; neoplasm staging